Cause-related marketing: it`s applicability in hypermarket context - Hong, Kay Tze; Ng, Siew Imm; Raja Yusof, Raja Nerina; Kaliappan, Shivee Ranjanee (Universiti Putra Malaysia, 2017)
The concept of cause-related marketing (CRM) was not sufficiently studied in the context of hypermarket. The objective of this study is to discover if CRM enhances customers’ patronage behaviour towards a hypermarket and whether the absence of CRM in a hypermarket initiates a switching behaviour among consumers. Therefore, five variables (attitude, CSR image, company-cause fit, education level and personal income) were examined for their influence on consumers’ patronage behaviour changes before and after the implementation of CRM. A total of 405 questionnaires were used for analysis. A paired-sample T-Test, one sample T-Test and multiple regression analyses were employed to analyse the research questions in this study. Results revealed that CRM implementation was able to produce two outcomes: customers’ patronage behaviour and customers’ switching behaviour. Also, factors such as attitude, CSR image and personal income were found to have different significant influences upon patronage behaviour increment across different hypermarkets.